2022
DOI: 10.3390/cancers14205043
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Targeted Photothermal Ablation of Epidermal Growth Factor Receptor-Expressing Cancer Cells with a Polypyrrole–Iron Oxide–Afatinib Nanocomposite

Abstract: Near-infrared–photothermal therapy (NIR-PTT) is a potential modality for cancer treatment. Directing photothermal effects specifically to cancer cells may enhance the therapeutic index for the best treatment outcome. While epithelial growth factor receptor (EGFR) is commonly overexpressed/genetically altered in human malignancy, it remains unknown whether targeting EGFR with tyrosine kinase inhibitor (TKI)-conjugated nanoparticles may direct NIR-PTT to cancers with cellular precision. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…A survey of European consumers found that NPs were present in over 2300 commercial products. Titanium dioxide (TiO 2 ), aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 ), carbon nanotubes, ZnO, ferrous oxide, ceric oxide, Au, and CuS are common NPs [82][83][84][85][86][87]. The majority of nanoparticles (NPs) exhibit biocompatibility and chemical inertness, with examples such as gold and titanium dioxide [88].…”
Section: Semiconductor-and Carbon-based Nanomaterialsmentioning
confidence: 99%
“…A survey of European consumers found that NPs were present in over 2300 commercial products. Titanium dioxide (TiO 2 ), aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 ), carbon nanotubes, ZnO, ferrous oxide, ceric oxide, Au, and CuS are common NPs [82][83][84][85][86][87]. The majority of nanoparticles (NPs) exhibit biocompatibility and chemical inertness, with examples such as gold and titanium dioxide [88].…”
Section: Semiconductor-and Carbon-based Nanomaterialsmentioning
confidence: 99%
“…When conjugating a biocompatible and photothermally conductive polymer (polypyrrole) to a TKI (afatinib) to direct near-infrared-photothermal therapy (NIR-PTT) in NSCLC, a research team found that polypyrrole-iron oxide-afatinib nanocomposite (PIA-NC) caused cancer cells to produce more reactive oxygen species (ROS), increased cytotoxicity, and minimized off-target biological effects of NIR-PTT [ 132 ].…”
Section: Nanoparticles Suitable For Nsclcmentioning
confidence: 99%
“…[ 7 ] By increasing the temperature of the surrounding tissue of photothermal agents through PTT, cell apoptosis (42–46 °C) or necrosis (>46 °C, thermal ablation) can be achieved, facilitating localized elimination of pathological tissue. [ 8,9 ] The near‐infrared (NIR) region is known as the biological window because NIR light has a relatively low absorption coefficient of biological systems and deep penetration capabilities, which can enable many nanoparticles (NPs) to produce photothermal activity, such as Au NPs and iron oxide NPs. [ 10 ] However, due to the small size of NPs and their rapid migration to the liver, spleen, and lung (>80%) as a result of blood circulation and metabolic scavenging, nanoparticle localization period and dosage in target tissues are not ideal.…”
Section: Introductionmentioning
confidence: 99%